2020
DOI: 10.3390/agronomy10111816
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Effects on Yield, Quality and Physiological Characteristics of Giant Rice

Abstract: In China, the quantity of nitrogen fertilizer applied is large, but as a consequence of a high level of loss, its utilization rate is low. Compared to common rice, the new giant rice has interesting characteristics, namely high biological yield and good efficient use of fertilizer. However, it becomes urgent to further consider the appropriate rate of nitrogen fertilizer to be applied. The giant rice varieties Feng5 and Feng6 were set up in a pot experiment and a field experiment under five doses of nitrogen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 13 publications
(10 reference statements)
4
23
0
1
Order By: Relevance
“…The deficiency of micronutrients (e.g., iron (Fe)) also affected numerous metabolic processes such as DNA synthesis, respiration, and photosynthesis [34,35]. As a result, the rice plant exposed to nutrient imbalance typically shows characteristic symptoms, such as poor root formation, thinner stems, folded leaves, pale green and dark brown necrotic spots, and yellow, burnt-orange and dying leaves, which ultimately lead to the retardation of normal growth and the decreases of tillering, panicle number, and yield ability of the rice [32][33][34][35][36][37]. For instance, nitrogen and phosphorous deficiency in soil can cause the decreases of rice photosynthesis, growth, development, yield, and grain storage product compositions (e.g., amylose and protein contents) [30,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficiency of micronutrients (e.g., iron (Fe)) also affected numerous metabolic processes such as DNA synthesis, respiration, and photosynthesis [34,35]. As a result, the rice plant exposed to nutrient imbalance typically shows characteristic symptoms, such as poor root formation, thinner stems, folded leaves, pale green and dark brown necrotic spots, and yellow, burnt-orange and dying leaves, which ultimately lead to the retardation of normal growth and the decreases of tillering, panicle number, and yield ability of the rice [32][33][34][35][36][37]. For instance, nitrogen and phosphorous deficiency in soil can cause the decreases of rice photosynthesis, growth, development, yield, and grain storage product compositions (e.g., amylose and protein contents) [30,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the rice plant exposed to nutrient imbalance typically shows characteristic symptoms, such as poor root formation, thinner stems, folded leaves, pale green and dark brown necrotic spots, and yellow, burnt-orange and dying leaves, which ultimately lead to the retardation of normal growth and the decreases of tillering, panicle number, and yield ability of the rice [32][33][34][35][36][37]. For instance, nitrogen and phosphorous deficiency in soil can cause the decreases of rice photosynthesis, growth, development, yield, and grain storage product compositions (e.g., amylose and protein contents) [30,[37][38][39]. Furthermore, soil potassium deficiency is a main cause of declines in translocation of photosynthetic products and other metabolites from leaves to pollen grains at the reproductive stage, resulting in spikelet sterility, unfilled grain percentage per panicle, reduced grain size and grain weight, and yield loss in rice [31,40].…”
Section: Introductionmentioning
confidence: 99%
“…It is said that tiller number determines the number panicles per plant [ 39 , 64 , 65 ], which happens to be an important yield component of rice. The number of tillers is influenced by environmental factors [ 66 ], agricultural practices, including nitrogen fertilization [ 67 , 68 , 69 , 70 , 71 , 72 ], or genetic factors [ 65 , 73 , 74 , 75 , 76 , 77 ]. It is also expected that an increase or decrease in tiller number per plant could cause significant changes in the shoot biomass.…”
Section: Discussionmentioning
confidence: 99%
“…It showed a positive correlation of R=1 in the N 120 treatment. Similarly, many studies have shown that rice yield increases with the increase of nitrogen application within a certain range, but the yield decreases when the nitrogen application is too high [39,40].…”
Section: Yield and Yield-related Parameters And Correlation Analysismentioning
confidence: 94%
“…Plant samples of all treatments were collected at four time points (10,25,40,55 days after treatment) in 2019. Fresh samples were used for morphological measurements and gene expression studies.…”
Section: Samplingmentioning
confidence: 99%